Three-dimensional analysis of the eggbeater kick in synchronized swimming - Homma, Ma.; Homma, Mi. (Biomechanics and Medicine in Swimming X, 2006)
One of the fundamental techniques in synchronized swimming is the eggbeater kick. The purpose of this study was to examine the kind of kinematic parameters that are reflected in an excellent eggbeater motion and, in particular, to evaluate the rotational angle of the hip. Nine Japanese elite synchronized swimmers served as subjects. The kinematics of the lower limbs and the hip rotational angle of each subject were quantified using three-dimensional video analysis. The hip almost rotated internally during the eggbeater kick. It was considered that the internal and external rotation movements of the hip were reflected in the foot abduction and adduction movements. This was because the phase of the angle curve between the hip rotation and foot abduction was almost identical in the reverse direction.